Twenty years later and the socialist heritage is still kicking: The case of Russia - Gur Ofer (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
Only recently, 20 years after transition to a market system, has Russia regained a similar production level it had achieved on the eve of transition in 1991. This may sound surprising, given its low productivity under central planning which dropped even lower during the last decades, and the rather high level of human capital inherited from the old regime, considered by many as the main engine of growth. The explanation may lie in Russia's difficulties and failure to transform the institutional infrastructure of the old regime to one that would support a market system and a democratic society, the second essential engine of growth. The paper surveys the difficulties of the institutional transformation using the 'new institutional economics' literature, and based on a number of international comparative studies provides evidence of the deep institutional weakness of Russia. Given the very high 'cost of transition', the question is raised whether the socialist growth strategy (as such) paid off.
Keywords: P30; P36; B52; T23; O50; 330; transition; institutions; Russia; economic growth; human capital; higher education; innovation